Global imbalances, the US dollar, and how the crisis at the core of global finance spread to "self-insuring" emerging market economies - Jörg Bibow (Levy Economics Institute of Bard College, 2010)
This paper investigates the spread of what started as a crisis at the core of the global financial system to emerging economies. While emerging economies had exhibited some resilience through the early stages of the financial turmoil that began in the summer of 2007, they have been hit hard since mid-2008. Their deteriorating fortunes are only partly attributable to the collapse in world trade and sharp drop in commodity prices. Things were made worse by emerging markets' exposure to the turmoil in global finance itself. As 'innocent bystanders,' even countries that had taken out 'self-insurance' proved vulnerable to the global 'sudden stop' in capital flows. We critique loanable funds theoretical interpretations of global imbalances and offer an alternative explanation that emphasizes the special status of the U.S. dollar. Instead of taking out even more self-insurance, developing countries should pursue capital account management to enlarge their policy space and reduce external vulnerabilities.
Keywords: E12; E43; E44; F02; F10; F32; F33; F42; 330; financial crisis; capital flows; self-insurance; capital controls; Bretton Woods II hypothesis; global saving glut hypothesis; Finanzmarktkrise; Reservewährung; Sparen; Zahlungsbilanzungleichgewicht; Ansteckungseffekt; Kapitalmarktliberalisierung; Regulierung; Bretton-Woods-System; Welt